Evaluation of the diagnostic capacities for emerging arboviral diseases in the international network MediLabSecure from 2014 to 2018 - Importance of external quality assessments - Guillain Mikaty; Séverine Matheus; Oliver Donoso Mantke; Elaine McCulloch; Heinz Zeichhardt; Jean-Claude Manuguerra; Jean-Claude Manuguerra (Elsevier, 2022)
Background: Emerging infectious diseases pose an increasing threat to all nations around the world, including to developed countries. By definition, because they are rare or unknown, public health systems are not well prepared against these emerging diseases. To be fully prepared, countries must have implemented surveillance systems to monitor rare or unusual sanitary events. Methods: The capacity of diagnostic laboratories is a key component of surveillance systems since they are in charge of identifying the pathogens responsible for outbreaks in a timely manner. The MediLabSecure project aims at implementing a comprehensive surveillance system for vector-borne diseases around the Mediterranean and Black Sea regions. From 2014 to 2018, the human-virology group of MediLabSecure notably supported the implementation of molecular diagnostic capacities for eight arboviruses and one coronavirus in 19 laboratories of its network through sharing of protocols and reagents, and technical training of the scientific staff of beneficiary laboratories. Results: We report the results of External Quality Assessments for four of these viruses to assess the efficiency of the diagnostic for these threats emerging in the geographic area. The results for these EQA demonstrate the success of the project in the implementation of diagnostic technics for the identification of Dengue, Chikungunya, Zika, and West Niles viruses in laboratories that did not have the capacity before. However, results also show that some work is still to be done to strengthen the newly acquired capacity. Conclusion: The MediLabSecure project deployed an effort to build an efficient capacity in identifying and survey the emergence of arboviruses in the Mediterranean area. Diagnostic technics were successfully implemented in many of the laboratories of the network, but the effort must be maintained over time to strengthen these capacities.